Livelihood corporation for climate resilience: Lessons from refugee host communities in Jordan - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
Jordan hosts over 3 million refugees while facing one of the harshest water scarcities in the world. Climate shocks are deepening. Resources are strained. And humanitarian aid often stops at the emergency phase. Without long-term livelihood support, both refugees and host communities risk getting trapped in cycles of dependency and tension. CGIAR Climate Security research highlights a quieter story unfolding in Jordan’s farming regions: how cooperation, not competition, can emerge when adaptation is local, inclusive, and sustained.